Quantitative estimation of some macro- and micro-minerals in follicular fluid of indigenous pigs - Chakraborty, D; Ray, S K; Datta, U; Mukhopadhayay, S K; Ganguly, S (The Indian Journal of Animal Sciences, 2012)
In the present study, characteristics of porcine follicular fluid (FF) harvested from different sized ovarian follicles and developmental competences of enclosed oocytes in relation to their sizes were investigated. It has been observed that some mineral components of FF like Ca, P, Cu and Fe significantly increased as the follicles increased in size, while only Li, which is first reported here in porcine FF decreased significantly with increase in follicular size. Therefore, it may enhance more success in reproduction in this species, which may improve the certain macro and micro mineral level in follicular fluid of oocytes.